2009
DOI: 10.1111/j.1464-5491.2008.02643.x
|View full text |Cite
|
Sign up to set email alerts
|

Continuous glucose monitoring as a tool to identify hyperglycaemia in non‐diabetic patients with acute coronary syndromes

Abstract: Aim To explore the occurrence and the distribution of glucose excursions > 7.8 mmol/l by continuous glucose monitoring (CGM) in non-diabetic patients admitted with acute coronary syndrome (ACS).Methods Twenty-one non-diabetic patients without baseline hyperglycaemia admitted for ACS wore a continuous glucose monitoring system (CGMS) for a median period of 45.6 h. Occurrence and 24-h distribution of time spent with blood glucose > 7.8 mmol/l (TS > 7.8) were retrospectively investigated.Results CGMS data disclos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 7 publications
0
9
0
1
Order By: Relevance
“…The development of continuous glucose monitoring system (CGMS) with a subcutaneous sensor device has provided a novel tool to record interstitial glycaemic kinetics [33]. GGMS revealed that normoglycaemia was only achieved 22% of the time in diabetic/non diabetic ICU patients [34] and that early and frequent hyperglycaemia occurred in non-diabetic patients with acute coronary syndromes [35]. Recent evidence suggests that continuous monitoring of glucose levels may help to signal glycaemic excursions and eventually to optimize insulin titration in the ICU [36].…”
Section: Lessons From Continuous Glucose Monitoringmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of continuous glucose monitoring system (CGMS) with a subcutaneous sensor device has provided a novel tool to record interstitial glycaemic kinetics [33]. GGMS revealed that normoglycaemia was only achieved 22% of the time in diabetic/non diabetic ICU patients [34] and that early and frequent hyperglycaemia occurred in non-diabetic patients with acute coronary syndromes [35]. Recent evidence suggests that continuous monitoring of glucose levels may help to signal glycaemic excursions and eventually to optimize insulin titration in the ICU [36].…”
Section: Lessons From Continuous Glucose Monitoringmentioning
confidence: 99%
“…Ideally, clinicians should not infuse any glucose solution during the management of such patients (except to correct hypoglycaemia) in order to avoid acute hyperglycaemia, which may be deleterious for the injured brain [7]. Even if CGMS has only been used to carefully evaluate post-stroke hyperglycaemia yet, this technology will probably be interesting in the future to manage hyperglycaemia in stroke unit in a more effective and safer manner [33], as in other critically ill patients [34][35][36].…”
Section: Practical Implications Regarding Glucose Management During Smentioning
confidence: 99%
“…In particular, these devices were highly sensitive in detecting rapid glucose excursions (12). Recently, these CGM techniques have also been evaluated in critically ill patients and have yielded similar positive results (1317). Mainly, subcutaneous CGM devices have been intensely investigated (1317).…”
mentioning
confidence: 92%
“…Radermecker et al ., studied the occurrence and the distribution of glucose excursions >7.8 mmol/l by CGMS in 21 non-diabetic patients admitted with acute coronary syndrome (ACS) without baseline hyperglycaemia. [49] CGMS data disclosed time spent >7.8 mmol/l in 17 patients, whereas only seven of them showed at least one capillary blood glucose test value above the threshold for the same time period. Glucose excursions were detectable earlier from CGMS data.…”
Section: Introductionmentioning
confidence: 99%